Solvent influence on non-adiabatic interfacial electron transfer at conductive oxide electrolyte interfaces - Aramburu Troselj, Bruno Martín (2020)
The kinetics for interfacial electron transfer (ET) from a transparent conductive oxide (tin-doped indium oxide, ITO, Sn:In2O3) to molecular acceptors 4-[N,N-di(p-tolyl)amino]benzylphosphonic acid, TPA, and [RuII(bpy)2(4,4′-(PO3H2)2-bpy)]2+, RuP, positioned at variable distances within and beyond the electric double layer (EDL), were quantified in benzonitrile and methanol by nanosecond absorption spectroscopy as a function of the thermodynamic driving force, -ΔG°. Relevant ET parameters such as the rate constant, ket, reorganization energy, λ, and electronic coupling, Hab, were extracted from the kinetic data. Overall, ket increased as the distance between the molecular acceptor and the conductor decreased. For redox active molecules within the Helmholtz planes of the EDL, ket was nearly independent of -ΔG°, consistent with a negligibly small λ value. Rips-Jortner analysis revealed a non-adiabatic electron transfer mechanism consistent with Hab < 1 cm-1. The data indicate that the barrier for electron transfer is greatly diminished at the conductor-electrolyte interface.